2019
DOI: 10.1183/13993003.02379-2018
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal organoids to model cystic fibrosis

Abstract: ERSpublicationsCF can be studied using patient-specific intestinal organoids. CFTR protein function in intestinal organoids correlates with clinical disease severity and drug testing in organoids could aid in finding drugs for people with rare CFTR mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In addition, the possibility of expanding iPSC-derived HIOs to an unlimited number, thanks to the maintenance of an intestinal stem-cell subpopulation, makes it very attractive for high-throughput screening in 384-well plates when combined with automated live microscopy. Indeed, pharmaceutical companies have already started to integrate intestinal organoids in their drugdiscovery pipeline 28 . It is important to keep in mind, however, that until exhaustive comparisons are performed, it cannot formally be ruled out that drug responses of certain CFTR variants can vary in a tissue-specific manner due to the recruitment of different cis-regulatory elements nearby or within the CFTR locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the possibility of expanding iPSC-derived HIOs to an unlimited number, thanks to the maintenance of an intestinal stem-cell subpopulation, makes it very attractive for high-throughput screening in 384-well plates when combined with automated live microscopy. Indeed, pharmaceutical companies have already started to integrate intestinal organoids in their drugdiscovery pipeline 28 . It is important to keep in mind, however, that until exhaustive comparisons are performed, it cannot formally be ruled out that drug responses of certain CFTR variants can vary in a tissue-specific manner due to the recruitment of different cis-regulatory elements nearby or within the CFTR locus.…”
Section: Discussionmentioning
confidence: 99%
“…The functionality of the FIS assay has been demonstrated in primary HIO obtained by crypt isolation during rectal biopsies 28 , but not in iPSC-derived organoids. We, therefore, introduced several modifications to the maturation step of the original differentiation protocol in order to generate iPSC-derived HIOs that more closely resembled biopsy HIOs (Figure 3C; manuscript in preparation).…”
Section: Directed Differentiation Of the Cftr Mutant And Corrected Ipscs Toward Cftr-expressing Intestinal Organoidsmentioning
confidence: 99%
“…A successful new feature in the journal is "ERJ methods" which was introduced in 2018 to give a guide to readers on the diverse and sometimes complex methodologies used in our speciality [42][43][44][45][46][47][48][49]. These are short mini-review papers intended to give non-experts the information required to understand and interpret the basics of cutting-edge methods.…”
Section: Erj Methods Are Taking Offmentioning
confidence: 99%
“…The use of human intestinal organoids grown from crypt fragments was characterized for the study of cystic fibrosis (CF), caused by mutations in the cystic fibrosis transmembrane conductance regulator gene (CFTR) that encodes epithelial anion channels (Dekkers et al 2016). Organoids have been used in preclinical studies to identify and develop CFTR modulating drugs and to study the mechanisms associated with differences in CFTR functioning (Van Mourik et al 2019). In a study on organoids by Dekkers et al, CFTR mutations and additional patient specific genetic traits were shown to modify the response to CFTR modulators (Dekkers et al 2016).…”
Section: Use Of Organoids As Test Systems For Drugs Screeningmentioning
confidence: 99%